PERBEDAAN FREKUENSI DIARE ANTARA BAYI YANG DIBERI ASI EKSKLUSIF DENGAN BAYI YANG DIBERI SUSU FORMULA PADA RENTANG USIA 2- 4 BULAN DI WILAYAH KERJA PUSKESMAS KLATEN TENGAH - Putri Rahmitasari; Burhannudin Ichsan; Sahilah Ermawati (Biomedika, 2012)
The main indicator of public healths degree is infant mortility rate (IMR). One of the main things that cause infant mortility is diarrhea. The existence of diarrheas incidence in infants can be caused due to errors in the form of food other than breast milk feeding at the age of 4 months or the practise of infant feeding with formula milk (replacement feeding). This research was an observational analytic research with cross sectional approach. Samples obtained amounted to 80 respondents who are infants aged 2-4 months in various posyandu in the area of Central Klaten. This sample had fulfiilled the predetermined criteria. The research instrument used a questionnaire. for the result, there were 21 respondents of 80 respondents obtained who had diarrhea. Respondents of exclusive breastfeeding who had frequency of diarrhea is rarely as many as 5 babies, whereas 1 baby for often category. Respondents of infant formula who had frequency of diarrhea is rarely as many as 12 babies, whereas 3 babies for often category. There were significant differences between infants who were breastfed exclusively with formula-fed infants againts diarrhea frequency indicated by the value of p = 0,032.Keywords: Frequency of Diarrhea, Exclusive Breast Feeding, Formula Feeding Infant, Infants Aged 2-4 Months